Navigating Cyber Law: Social Media Dynamics - Hamid, Siti Nur Cholisa; Purwaningsih, Sri Budi; Indakto, Ratro (Proceedings of The ICECRS, 2023)
This research investigates the intersection of Cyber Law and Social Media through an extensive analysis of scholarly articles, aiming to understand the evolving landscape of digital interactions and their legal implications. Utilizing Lens.org, the study initiated with a keyword search "Cyber OR Cyber Law AND Social Media" in scholarly works, yielding a vast dataset of 187,637 academic works. After meticulous filtering, focusing on journal articles within the legal domain, 30,797 pertinent studies were identified. The analysis delves into top institutions, revealing The University of Sheffield as a prolific contributor, especially in the field of Sociology. The study's temporal analysis highlights a peak in scholarly output in 2018, emphasizing the dynamic nature of social media-related legal discourse. Sociology emerged as the dominant field of study, with contributions from esteemed institutions such as London School of Economics and Political Science. The most active authors, including Mark D Griffiths and Crihs D Geddes, exhibited substantial engagement in this domain. Geographically, the United States emerged as a key player, with 26,991 journal articles dedicated to the topic. Springer Nature stood out as the leading publisher, reflecting the substantial scholarly focus on social media. This dataset offers invaluable insights for legal scholars, policymakers, and social scientists, shedding light on the intricate relationship between cyber law and social media, thus paving the way for informed legal frameworks and societal interventions. Highlights : Prolific Output: The study uncovers 30,797 scholarly works at the intersection of Cyber Law and Social Media, highlighting the depth of research in this domain. Dynamic Discourse: Scholarly output peaked in 2018, indicating the evolving nature of social media-related legal discussions and the need for current and adaptable legal frameworks. Global Perspectives: Contributions from institutions worldwide, especially in Sociology, emphasize the global relevance of social media-related legal research, urging for international collaboration and legal harmonization. Keywords: Cyber Law, Social Media, Legal Implications, Digital Interactions, Societal Impact